1967
DOI: 10.1029/jz072i024p06137
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and emission in the 8-millimeter region by ozone in the upper atmosphere

Abstract: The absorption of solar radiation and the emission from the atmosphere (effective sky temperature) were measured over the ranges of the millimeter region corresponding to rotational lines of ozone centered at 30,056, 36,025, and 37,830 Mhz. The measurements were made possible by the special development of a frequency-switching radiometer and a gain-compensation technique. The contributions of ozone to atmospheric absorption and emission are evaluated from the solution of the radiative transfer equation on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…At present five resonances in the terrestrial atmosphere have been observed. Mouw and Silver [35] observed the 36.025-GHz line in absorption against the sun, Caton et al [31] observed the 37.836-GHz line in absorption and the 30.056-GHz line in emission, Barrett et al [36] observed the 23.861-GHz line in emission, and Caton et al [32] observed the 101.737-GHz line in both emission and absorption. For spectral resolution of a few megahertz, the line amplitudes in emission at zenith are generally a few tenths of a degree Kelvin except for the line at 101.737 GHz, which had an amplitude of a few degrees.…”
Section: Tb(v) = + J:-xt(z)mentioning
confidence: 99%
“…At present five resonances in the terrestrial atmosphere have been observed. Mouw and Silver [35] observed the 36.025-GHz line in absorption against the sun, Caton et al [31] observed the 37.836-GHz line in absorption and the 30.056-GHz line in emission, Barrett et al [36] observed the 23.861-GHz line in emission, and Caton et al [32] observed the 101.737-GHz line in both emission and absorption. For spectral resolution of a few megahertz, the line amplitudes in emission at zenith are generally a few tenths of a degree Kelvin except for the line at 101.737 GHz, which had an amplitude of a few degrees.…”
Section: Tb(v) = + J:-xt(z)mentioning
confidence: 99%